2021
DOI: 10.1101/mcs.a006085
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the genotypic spectrum of ACTG2-related visceral myopathy

Abstract: Visceral myopathies (VMs) encompass a spectrum of disorders characterized by chronic disruption of gastrointestinal function, with or without urinary system involvement. Pathogenic missense variation in smooth muscle γ-actin gene ( ACTG2 ) is associated with autosomal dominant VM. Whole-genome sequencing of an infant presenting with chronic intestinal pseudo-obstruction revealed a homozygous 187 bp (c.589_613 + 163del188) deletion spanning the exon 6–intron 6 boundary within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Some investigators specifically noted an absence of histological abnormalities. [3][4][5][6][7] Others reported a variety of other putative alterations in the muscularis propria including thinning of one or both muscle layers, [8][9][10] "vacuolar change", 7,9,11 intestinal neuronal dysplasia type B, 12 aplastic desmosis, 12 "disorderly arranged intramyenteric neural tissue", 13 nuclear palisading, 9 haphazard arrangement of smooth muscle cells, 13,14 muscle degeneration and fibrosis, 15 intracellular inclusion bodies, 16,17 and cytoplasmic aggregates or clumps of ACTG2-immunoreactive material. 10,16 These divergent findings prompted us to conduct a light and electron microscopic and immunohistochemical study of intestinal specimens from a series of 16 patients with pathogenic ACTG2 variants, in an effort to identify potentially distinctive features for patients with this form of visceral myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators specifically noted an absence of histological abnormalities. [3][4][5][6][7] Others reported a variety of other putative alterations in the muscularis propria including thinning of one or both muscle layers, [8][9][10] "vacuolar change", 7,9,11 intestinal neuronal dysplasia type B, 12 aplastic desmosis, 12 "disorderly arranged intramyenteric neural tissue", 13 nuclear palisading, 9 haphazard arrangement of smooth muscle cells, 13,14 muscle degeneration and fibrosis, 15 intracellular inclusion bodies, 16,17 and cytoplasmic aggregates or clumps of ACTG2-immunoreactive material. 10,16 These divergent findings prompted us to conduct a light and electron microscopic and immunohistochemical study of intestinal specimens from a series of 16 patients with pathogenic ACTG2 variants, in an effort to identify potentially distinctive features for patients with this form of visceral myopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The noncoding ACTG2 exon 1 is typically not captured in standard ES. This is also illustrated by James et al (7), in which GS detected a homozygous exonic variant that was missed by 2 copy number and indel variant callers.…”
Section: Actg2-related Visceral Myopathy In Brothersmentioning
confidence: 64%
“…This patient was dependent on parenteral nutrition, presenting with infantile periodic abdominal pain, vomiting and growth deficiency. Most recently, James et al ( 7 ) reported a homozygous exon 6 deletion c.589_613 + 163del188 in a 13-month-old boy with severe visceral myopathy. We speculate that the exon 1 deletion of ACTG2 leads to loss-of-function, supported by their father’s chronic diarrhea and a small decrease of intestinal ACTG2 expression in the brothers, although the immunohistochemistry results need to be interpreted with care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin gamma smooth muscle 2 (ACTG2) gene ((LRI = 0.015873), belonging to the actin protein family, is imperative for maintaining the cytoskeleton through the regulation of cell movement and muscle contraction 86 . Genome sequencing studies have revealed that a homozygous and a heterozygous variant of ACTG2 is associated with gastrointestinal dysfunction 87 . Studies have demonstrated that the over-expression of ACTG2 has been found to play a critical role in the progression of hepatocellular carcinoma 88 and bladder cancer 89 .…”
Section: Genesmentioning
confidence: 99%